Long-term trends in ocean plankton production and particle export between 1960–2006 - C. Laufkötter; M. Vogt; N. Gruber (Biogeosciences, 2013)
We analyse long-term trends in marine primary and particle export production and their link to marine phytoplankton community composition for the period 1960–2006 using a hindcast simulation of the Biogeochemical Elemental Cycling Model coupled to the ocean component of the Community Climate System Model. In our simulation, global primary and export production decrease significantly over the last 50 yr, by 6.5% and 8% respectively. These changes are associated with an 8.5% decrease in small phytoplankton biomass and 5% decrease in zooplankton biomass. Diatom biomass decreases globally by 3%, but with strong temporal and spatial variability. The strongest decreases in primary and export production occur in the western Pacific, where enhanced stratification leads to stronger nutrient limitation and a decrease in total phytoplankton. The concurrent decrease in diatom fraction and in zooplankton biomass causes a lower export efficiency in this region. Substantial phytoplankton composition changes also occur in the Southern Ocean and North Atlantic, although these are masked in part by a high degree of interannual variability. In these regions, stronger wind stress enhances mixing, reducing the biomass of small phytoplankton, while diatoms profit from higher nutrient inputs and lower grazing pressure. The relative fraction of diatoms correlates positively with the export efficiency (r = 0.8, p < 0.05) in most areas except for the North Pacific and Antarctic Circumpolar Current, where the correlation is negative (r = –0.5, p < 0.05). However, the long-term trends in global export efficiency are ultimately driven by the reduction in small phytoplankton and particularly decreases in coccolithophore biomass. The diagnosed trends point toward a substantial sensitivity of marine primary production and export to climatic variations and trends.